Relevansi Konsep Humanis Ibnu Khaldun dengan Praktik Pendidikan Islam Kontemporer: Studi Kasus di Madrasah Aliyah Al Hikmah Bandar Lampung - Heri Aulia Rahman (CV. Eureka Artha Nusantara, 2026)
This study aims to analyze the relevance of Ibn Khaldun's concept of humanistic education to contemporary Islamic educational practices through a case study at Madrasah Aliyah Al Hikmah Bandar Lampung. Previous studies have extensively discussed Ibn Khaldun's educational philosophy from theoretical and conceptual perspectives. However, limited research has examined its practical implementation in contemporary Islamic educational institutions, particularly in integrating intellectual, spiritual, and social dimensions within the learning process. This study addresses this gap by exploring the extent to which Ibn Khaldun's humanistic educational principles are reflected in educational practices at the madrasah level. A qualitative case study approach was employed. Data were collected through participant observation, in-depth interviews with teachers, students, and the principal, as well as document analysis of the curriculum and learning activities. The findings reveal that the educational practices at MA Al Hikmah Bandar Lampung substantially align with Ibn Khaldun's humanistic educational principles, including the integration of religious and general knowledge, gradual learning, teacher role modeling, and attention to students' social contexts. Nevertheless, several challenges remain, particularly regarding limited educational resources and resistance to the adoption of innovative teaching methods. This study concludes that Ibn Khaldun's educational thought remains highly relevant for strengthening humanistic and contextual Islamic education. The novelty of this research lies in its empirical examination of Ibn Khaldun's educational philosophy within the context of a contemporary Islamic secondary school, providing practical evidence of the continued applicability of his ideas in modern Islamic education.